(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Digital Currency is a latest invention in banking system with that every citizens came in to the economy. For for trading every citizen are using digital payment system but investing purpose countries central banks has introduced a digital Currency. Every country has its own central bank and all banks works unde its own central banks norms. Likewise the following banks of different Countries and its central bank names the following are the some of them: Indian Central Bank Reserve Bank of India, European Central Bank Bank of Japan Sovereigns Riks bank, Swiss National Bank Bank of England, Board of Governors Federal Reserve System Bank for International Settlements Bank of Canada. Every bank has its own currencies like Reserve Bank of India Rupees,